LEPIDOPTERA DAN PARASITOID YANG BERASOSIASI PADA TANAMAN KENANGA (CANANGA ODORATA (LAM.) HOOK.F. & THOMSON) - Maidatun Kamilah Hilamawati; Retno Wijayanti (Universitas Sebelas Maret, 2010)
The objectives of this research are to identify the Lepidoptera and parasitoid that associated on C. odorata. The research was conducted in Laboratory of Pest and Disease of Crop of Agriculture Faculty UNS and in C. odorata plantation in Banyudono, Boyolali Regency, Central Java. Observation was done at seedling and crop yield. Lepidoptera (larvae, pupae, adult) and parasitoids that found were taken to be identified in laboratory. Larvae and pupae which infected by parasitoid or pathogen placed in separated jar to be kept and waited for parasitoid emerged. Collection of Lepidopteras and parasitoids were identified by comparing with picture, using key of determination, and combination both of them. Identifying was done at family and several of them at species.In this research was found eight species of Lepidopteras and two parasitoids. Eight species of Lepidopteras consist of species of family Lymantridae, Nymphalidae, Papilionidae, Satyridae, Psychidae, and Saturniidae (Cricula trifenestrata and Attacus atlas). Two parasitoid were Apanteles sp. and Pteromalus sp.)